Nurses' attitudes towards the use of PRN psychotropic medications in acute and forensic mental health settings. - Barr, L.; Wynaden, Dianne; Heslop, K. (Wiley-Blackwell Publishing Asia, 2017)
Many countries now have national mental health policies and guidelines to decrease or eliminate the use of seclusion and restraint yet the use of Pro Re Nata (PRN) medications has received less practice evaluation. This research aimed to identify mental health nurses' attitudes towards the use of PRN medications with mental health consumers. Participants were working in forensic mental health and non-forensic acute mental health settings. The "Attitudes towards PRN medication use survey" was used and data were collected online. Data were analysed using the Statistical Package Social Sciences, Version 22.0. Practice differences between forensic and other acute mental health settings were identified related to the use of PRN medications to manage symptoms from nicotine, alcohol and other drug withdrawal. Differences related to the useage of comfort rooms and conducting comprehensive assessments of consumers' psychiatric symptoms were also detected. Qualitative findings highlighted the need for increased accountability for the prescribing and administration of PRN medications along with more nursing education/training to use alternative first line interventions. Nurses administering PRN medications should be vigilant regarding the indications for this practice to ensure they are facilitating the consumer's recovery by reducing the use of all forms of potentially restrictive practices in the hospital setting. The reasons for using PRN medications and PRN administration rates must be continually monitored to avoid practices such as high dose antipsychotics use and antipsychotic polypharmacy to ensure the efficacy of the consumers' management plans on their health care outcomes.